Agriculture Economic Recovery dan Ketahanan Pangan Kabupaten Lamongan pada Saat Pandemi Covid-19 - Setiani, Salsa Yuli; Zain, Iqbal Abdul Aziz; Pratiwi, Tika (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2023)
The Covid-19 pandemic has caused instability in all sectors of the economy, especially in the agricultural sector. Lamongan Regency is one of the provinces in East Java which has the largest rice and rice yields in East and National Java. With this achievement, it is hoped that Lamongan Regency can maintain food security in the region. This study uses a qualitative descriptive analysis, the purpose of this study is to analyze the conditions and the role of the community and the government in the economic recovery of Lamongan Regency during Covid19 so that the food supply in the region remains fulfilled. The results of this study indicate that food conditions in Lamongan Regency are quite fulfilled during the pandemic, this is evidenced by the increase in harvest yields every year. The efforts of the community and the government of Lamongan Regency are to always pay attention to the distribution of food needs and the welfare of farmers in the Lamongan Regency area properly.